Examining personality factors and character defenses assists in the differentiation between college students with Internet addiction and unaffected controls. (November 2015) - Floros, Georgios; Siomos, Konstantinos; Antoniadis, Diomidis; Bozikas, Vasileios-Panteleimon; Hyphantis, Thomas; Garyfallos, Georgios
Abstract: The purpose of this study is to evaluate the predictive value of personality factors, character defenses and psychopathology indexes in discerning between a clinical sample of Internet-addicted college students and a random sample of non-addicted college students. A discriminant analysis identified the variables which enabled discerning Internet addicts from non-addicts in 78% of all subjects. Internet-addicted students presented with higher frequency of connecting to the Internet, more time spent online, higher impulsivity, higher help-rejecting complaining and lower sublimation. Indexes of overt symptomatology did not assist in discerning clinical cases from controls. In conclusion, employing a test battery which includes not only measures of Internet addiction but also measures of inheritable personality factors and character defenses can be of assistance both in clinical work and in epidemiological research. Highlights: Comparison of a clinical sample of 50 students with IAD to a control sample Higher impulsivity, help-rejecting complaining and lower sublimation discerned IAD. Indexes of psychopathology did not contribute to the final discriminant model. Measures of personality and character are helpful in IAD research.